2017
DOI: 10.1007/s10787-017-0393-5
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory basis of antioxidant therapy and its future prospects: an appraisal

Abstract: Antioxidants are agents which can modulate oxidant-antioxidant profile of body system by neutralizing pro-oxidant molecules. The current scientific knowledge on mechanisms of antioxidant activity of biomolecules was critically reviewed with a special emphasis on immunomodulation. The immuno-oxidative wreckage of animals in various disease conditions and the role of biomodulators in curbing the oxidative stress through immune pathways were analyzed. The critical role of immunomodulatory mechanisms in controllin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 105 publications
0
14
0
Order By: Relevance
“…The present study explains that the antioxidant therapy can curb this pathological mechanism by modulating oxidative metabolisms preventing exhaustive damage to â cells. Similarly, the modulation of host immune mechanisms by the antioxidant N-acetylcysteine in Th1 cytokine dominant disease conditions was previously suggested by Ajith et al (2017). Also, the human form of IDDM is usually considered as a Th1 dominant condition with increased expression of Th1 cytokines (Eizirik et al 2009).…”
Section: Resultsmentioning
confidence: 82%
“…The present study explains that the antioxidant therapy can curb this pathological mechanism by modulating oxidative metabolisms preventing exhaustive damage to â cells. Similarly, the modulation of host immune mechanisms by the antioxidant N-acetylcysteine in Th1 cytokine dominant disease conditions was previously suggested by Ajith et al (2017). Also, the human form of IDDM is usually considered as a Th1 dominant condition with increased expression of Th1 cytokines (Eizirik et al 2009).…”
Section: Resultsmentioning
confidence: 82%
“…A clinical challenge is to achieve transplants that integrate advanced functional biomaterials with stem cells and biological regulators (such as antimicrobial, immunomodulatory, and trophic compounds) [ 253 ]. Redox equilibrium can be a key player in modulating these regulators; namely, the antioxidants can play a central role as immunomodulators [ 254 ]. A promising assumption in post-operation could be derived from an augmented bioavailability in the human body of natural products in association with standard pharmaceutical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…infested treatment groups on day 0 and day 28 The current study showed that bubaline pediculosis caused by H. tuberculatus infestation had severe oxidative stress, anaemia, leukocytosis with neutrophilia, eosinophilia and lymphocytopenia. Other ectoparasitic infestations in various domestic animals; ovine pediculosis (Dede et al, 2002), pediculosis in goats (Ajith et al, 2017b), pediculosis in buffaloes (El-Moghazy, 2011), generalized canine demodicosis (Dimri et al, 2008), psoroptic mange infection in sheep (Aktas et al, 2017), sarcoptic mange in domestic goats (De and Dey, 2010), dogs (Behera et al, 2011;Singh and Dimri, 2013) and dairy buffaloes (Dimri et al, 2007) had similar oxidative stress and haematological changes observed in bubaline pediculosis. Growing body of evidence from recent studies promises the potential use of antioxidants for prophylactic and therapeutic management of various infectious diseases.…”
Section: Table1 Mean Lice Count In Different Body Regions Of Sucking Lice (Haematopinus Tuberculatus)mentioning
confidence: 99%